Global map of clay minerals in terrestrial soils - Akihiko Ito; Rota Wagai (PANGAEA, 2016)
We developed a comprehensive dataset of major soil clay minerals covering the global land surface for both topsoil (near-surface) and subsoil at different spatial resolutions. This dataset is intended for application in a variety of earth science fields that require interdisciplinary data. We gathered observational data on clay minerals through a literature survey and meta-analysis. Most observations were originally obtained by x-ray diffraction (XRD) analysis. The multitude of clay minerals that occur in soils were classified into ten groups: chlorite, gibbsite, kaolinite, mica-illite, smectite, quartz, vermiculite, non-crystalline (amorphous and short-range order minerals), iron oxide, and others. We then aggregated the clay mineral composition data on the basis of 12 soil orders. Using a global map of soil orders and additional soil datasets, we developed global maps of clay mineral abundances in topsoil and subsoil at a resolution of 2° grid cells (about 3.7 km) and, by averaging, at lower spatial resolutions (e.g., 1° grid cells). We examined uncertainties in the dataset by statistical (i.e., Monte Carlo) methods and by comparison with previous datasets. The new dataset will facilitate continental-scale studies of biogeochemistry and climatology by providing more precise soil properties related to, for example, soil adsorption and dust emission. The dataset should also find application in interdisciplinary studies in fields such as hydrology and agronomy, both as input data for model simulations and for the interpretation of observational data.